METODE TOPSIS DALAM PENERAPAN KELUARGA HARAPAN (PKH) DI DESA KOTABATU KECAMATAN CIOMAS KABUPATEN BOGOR: METODE TOPSIS DALAM PENERAPAN KELUARGA HARAPAN (PKH) DI DESA KOTABATU KECAMATAN CIOMAS KABUPATEN BOGOR - Martua Hami Siregar; Helina Apriyani; Sismadi Sismadi (Institute of Computer Science (IOCS), 2019)
PKH or the Family Hope Program is a social protection program through the provision of non-cash money to Very Poor Households (RTSM). The purpose of the Family Hope Program is to reduce numbers and break the chain of poverty, improve the quality of human resources, and change behaviors that do not support the welfare of the poorest groups. The problem in this assistance program is that sometimes families who are not eligible for assistance mean that they are not from the family group with the category of Very Poor Households (RTSM) but get assistance from the Hope Family Program (PKH) so that assistance is not on target. The method used is TOPSIS (Technique for Others Reference by Similarity to Ideal Solution) is one method that can help the optimal decision making process to solve problems with various alternative selection criteria. The results showed that the final preference value obtained a value of 0.42 as the maximum value. It means that the criteria for the proposed Family Assistance Program are expected to be given on the basis of criteria, namely the family that send their children to a certain level of attendance, check their health and or pay attention to the nutritional adequacy and healthy lifestyle of children and pregnant women (Y2)